(untitled) (Práxis Educativa, 2024)
Given the educational significance of using technological tools such as calculators in mathematics learning, it is essential that future teachers possess the necessary knowledge and skills to harness their potential. This study focuses on exploring the mathematical and technological knowledge of future primary education teachers, as well as their beliefs about the use of calculators as an educational tool. A mixed methodology is employed with a specially designed questionnaire (n=65) that helps to understand their beliefs and self-concept regarding the didactic use of calculators. Additionally, tasks are included that require the mobilization of technological-mathematical knowledge. The results highlight the need for more effective training in the use of calculators, integrating didactic-mathematical education with technological training.